BUDAYA SPIRITUAL KESULTANAN BANJAR: HISTORISITAS DAN RELEVANSINYA DI MASA KINI - Buseri, Kamrani (Pascasarjana UIN ANTASARI Banjarmasin, 2011)
This paper discusses about the spiritual culture in Kesultanan Banjar seeing from the historical perspective and its relevancy with the life today. The spiritual culture in banjar society can be seen from life cycle since birthday till die. Many of them were modified and fitted with the Islamic teaching. So that, the Islamic dimension is more explicit that the culture one. Kesultanan in varies cultural events ought to make the understanding to the society that Kesultanan Banjar is very concern to the spiritual culture and give the meaning for a material culture developing in many aspect of life. Besides, in any opportunity it may put the strength spiritual culture programm in order to be implemented in many sides of development.